2021
DOI: 10.1108/ijhrh-09-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Assessing unmet health-care needs of the elderly in west of Iran: A case study

Abstract: Purpose The purpose of this study is to investigate the status of perceived need, seeking behavior and utilization of health services in the elderly population of Sanandaj (west of Iran). Design/methodology/approach This is a cross-sectional study conducted on 800 elderly people in Sanandaj. Subjects were selected using multistage sampling and data were collected using self-report questionnaires. A multivariate logistic model with odds ratios (ORs) was used to determine the relationship of independent variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Unmet health care need is a longstanding problem especially in underdeveloped areas, which is further deteriorated during the pandemic. [49][50][51] This study reveals how the pandemic-induced health care resource shortages impact the mental health problem among older people and compares such effect among them with different work patterns. Previous studies document the association between unmet health care needs and the presence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Unmet health care need is a longstanding problem especially in underdeveloped areas, which is further deteriorated during the pandemic. [49][50][51] This study reveals how the pandemic-induced health care resource shortages impact the mental health problem among older people and compares such effect among them with different work patterns. Previous studies document the association between unmet health care needs and the presence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the stream of studies proposing the beneficial effect of postponing retirement, this study provides empirical evidence that late retirement could contribute to health maintenance among older adults by maintaining their social and occupational status and gaining social support. In emerging economies where universal healthcare coverage has not achieved, unmet health care need amongst older people is prevalent 30 . As such, the social health insurance would be a most important solution for older people to cope with out‐of‐pocket health expenditure in developing countries 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 2 (Continued) coverage has not achieved, unmet health care need amongst older people is prevalent. 30 As such, the social health insurance would be a most important solution for older people to cope with out-of-pocket health expenditure in developing countries. 31,32 The employment-based social health insurance could help reduce economic burdens on older adults and facilitate personal health management, due to the greater reimbursement rate of medical expense and a larger reimbursement scope of medicines.…”
Section: Direct Effectmentioning
confidence: 99%
“…Moreover, this study also found that the UEBMI could weaken the jointly contributing effect of PFL and difficulty in IADLs on withdrawal from late career participation among late retirees. Prior studies show that the healthcare needs of vulnerable populations who face catastrophic health expenditures are often unmet [ 43 46 ]. Therefore, the level of reimbursement needs to be improved for common diseases that cause PFL and difficulty in IADLs in the aged, such as chronic back pain, knee and hip joint replacement, cerebrovascular accident and coronary heart disease [ 7 ].…”
Section: Discussionmentioning
confidence: 99%